Phase II trial of the Sigma-1 receptor agonist cutamesine (SA4503) for recovery enhancement after acute ischemic stroke - Urfer, Roman; Moebius, Hans J; Skoloudik, David; Santamarina, Estevo; Sato, Wakao; Mita, Shiro; Muir, Keith W (Stroke, 2014)
BACKGROUND AND PURPOSE: The σ-1 receptor (Sig-1R) agonist cutamesine (SA4503) enhanced functional recovery after experimental stroke with a treatment initiation window of 48 hours and chronic treatment for 28 days. We conducted a phase 2 clinical trial exploring the safety, tolerability, dose range, and functional effects of cutamesine in patients with ischemic stroke. METHODS: Subjects were randomized between 48 and 72 hours after stroke to receive cutamesine 1 mg/d, 3 mg/d, or placebo for 28 days. Effects on safety and function were assessed at baseline, at end of treatment (day 28), and at end of follow-up (day 56). RESULTS: In 60 patients, treatment with both cutamesine dosages was safe and well tolerated without significant differences in numbers of treatment emergent or serious adverse events. No significant effect was observed on the primary efficacy measure (change in National Institutes of Health Stroke Scale from baseline to day 56) or modified Rankin Scale and Barthel Index scores. Post hoc analysis of moderately and severely affected patients (baseline National Institutes of Health Stroke Scale, ≥7 and ≥10) showed greater National Institutes of Health Stroke Scale improvements in the 3 mg/d cutamesine group when compared with placebo (P=0.034 and P=0.038, respectively). A trend toward a higher proportion being able to complete a 10m timed walk was observed for cutamesine-treated subjects. CONCLUSIONS: Cutamesine was safe and well tolerated at both dosage levels. Although no significant effects on functional end points were seen in the population as a whole, greater improvement in National Institutes of Health Stroke Scale scores among patients with greater pretreatment deficits seen in post hoc analysis warrants further investigation. Additional studies should focus on the patient population with moderate-to-severe stroke. CLINICAL TRIAL REGISTRATION URL: http://www.clinicaltrials.gov/show/NCT00639249. Unique identifier: NCT00639249. The EudraCT number is 2007-004840-60 (https://www.clinicaltrialsregister.eu/ctr-search/trial/2007-004840-60/GB).
Keywords: dospělí; Receptors, sigma; Female; Adult; ženské pohlaví; piperaziny; cévní mozková příhoda; Time Factors; časové faktory; receptory sigma; Internationality; lidé; dvojitá slepá metoda; radioizotopy uhlíku; Recovery of Function; Stroke; internacionalita; Aged, 80 and over; ischemie mozku; obnova funkce; Carbon Radioisotopes; Double-Blind Method; Male; Aged; Piperazines; Brain Ischemia; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; Humans